Japanese management accounting system as a competitive tool : a case study of a national automobile supplier in Malaysia / Normah Haji Omar, Ibrahim Kamal Abdul Rahman and Saiful Anuar Sabaruddln - Omar, Normah; Abdul Rahman, Ibrahim Kamal; Sabaruddln, Saiful Anuar (Faculty of Accountancy & Accounting Research Institute (ARI), 2002)
In its effort to become a "world class" supplier, comparable to its Japanese counterparts, the company chosen for the current case study had successfully emulated the Japanese management accounting technique known as the "lean production system". This system encompasses a combination of techniques such as Just-in-Time (JIT), Total Quality Management (TQM), Continuous Improvement, Zero defect, Statistical Control Analysis, Kaizen and Supply Chain Analysis. Lean production system reinforbes the emphasis of competitiveness in the culture of this company. The study found that the lean production system had provided a solution for the company to pursue a manufacturing-based competitive advantage by creating order winners and differentiating the company from the competitors. The technique was also found to support the company's competitive strategy.